Association of Chlamydia trachomatis, C. pneumoniae, and IL-6 and IL-8 Gene Alterations With Heart Diseases - Almeida, Nubia Caroline Costa; Queiroz, Maria Alice Freitas; Lima, Sandra Souza; Brasil Costa, Igor; Ayin Fossa, Marco Antonio; Vallinoto, Antonio Carlos R.; Ishak, Marluísa de Oliveira Guimarães; Ishak, Ricardo (Frontiers in Immunology, 2019)
Atherosclerosis is a progressive disease characterized by chronic inflammation of the arterial walls, associated with genetic and infectious factors. The present study investigated the involvement of Chlamydia trachomatis and C. pneumoniae infections and immunological markers (C-reactive protein, CRP, TNF-α, IL-6, IL-8, and IL-10) in the process of atherosclerosis. The evaluation included 159 patients for surgical revascularization (CAD) and 71 patients for surgical heart valve disease (HVD) at three hospitals in Belém, Brazil. The control group (CG) comprised 300 healthy individuals. Blood samples collected before surgery were used for antibodies detection (enzyme immunoassay), CRP (immunoturbidimetry) and IL-6 levels (enzyme immunoassay). Tissue fragments (atheroma plaque, heart valve and ascending aorta) were collected during surgery and subjected to qPCR for detection of bacterial DNA. Promoter region polymorphisms of each marker and relative quantification of TNF-α, IL-8, and IL-10 gene expression were performed. Demography and social information were similar to the general population involved with both diseases. Antibody prevalence to C. trachomatis was 30.6%, 20.3% and 36.7% (in the CAD, HVD and CG, respectively) and to C. pneumoniae was 83.6%, 84.5% and 80.3% (in the CAD, HVD and CG, respectively). C. trachomatis cryptic plasmid DNA was detected in 7.4% of the samples. Frequency of IL-6-174G>C polymorphism was higher in CAD and HVD than in CG regardless of previous exposure to Chlamydia. Previous C. trachomatis infection showed involvement in HVD and CAD. Significant association between disease and previous C. pneumoniae infection was found only among HVD. GG genotype of IL-6-174G>C is apparently a risk factor for heart disease, whereas AT genotype of IL-8-251A>T was mainly involved in valvulopathies, including patients with prior exposure to C. pneumoniae.